Application of Grid Task Scheduling Algorithm RR to Medium-Grained Evolution Strategies - Matsumura, Y.; Oiso, M.; Matsuda, M.; Ohkura, K.; Fujimoto, N.; Hagihara, K.; Wyatt, J.; Xin Yao (Third International Conference on Natural Computation (ICNC 2007), 2007)
A computational method for implementation of Evolution Strategies (ES) in Grid computing environments is discussed. In this paper, list scheduling with Round-robin order Replication (RR) is adopted to reduce waiting times due to synchronization in Medium-grained ES. Our results show that the replication in RR can reduce the synchronous waiting time in comparison with Work Queue (WQ) methods.